A Study on Impact of a Clinical Pharmacist in Improving Knowledge of Cardiology Out-patients about Oral Anticoagulants - K N, Anila; J, Emmanuel (Indian Journal of Pharmacy Practice)
The study was conducted to find the magnitude of impact of a clinical pharmacist in improving knowledge of cardiology patients about oral anticoagulants. The interventional group received an additional care by the clinical pharmacist and was compared with a control group which received only the usual care of the physician. Patients in the intervention group were assessed for their baseline knowledge using validated questionnaire about the use of anticoagulants and counseled regarding the use of oral anticoagulants, side effects, dietary recommendations, importance of INR (International normalised ratio) tests and dose titrations, compliance and provided information booklets and contact numbers for reporting INR results and reassessed during their follow up. There was statistically significant improvement in knowledge score of patients in the intervention group as compared to control group and statistically significant increase in the number of INR's within target range for the patients in intervention group as compared to control group. The intervention group showed much better improvement in knowledge score (p<0.05) which was evident by the mean difference which had an increase of 5.864 points compared to control group's 0.907 points. The fraction of INRs within therapeutic range indicated better anticoagulation control in the intervention group compared to control group (0.632 vs 0.432). This study showed that knowledge of patients regarding oral anticoagulation therapy was insufficient before the clinical pharmacist's involvement. Counseling by a clinical pharmacist will improve the outcome of the patients taking oral anticoagulants as evidenced by the increase in the values of INRs and showed better anticoagulation control.
Keywords: Clinical pharmacist; patient knowledge; oral anticoagulants; knowledge